The contribution of drug import to the cost of tuberculosis treatment: a cost analysis of longer, shorter and short drug regimens for Karakalpakstan, Uzbekistan [research data] - Kohler, Stefan; Sitali, Norman; Achar, Jay; Paul, Nicolas (Universität, 2024)
Tuberculosis (TB) programs depend on a continuous supply of large amounts of high-quality TB drugs. When TB programs procure TB drugs from international suppliers, such as the Global Drug Facility, they can incur import costs for international transport, customs clearance, and national transport. We assessed the drug costs and import costs of 18 longer (≥18 months), 10 shorter (9-12 months), and 8 short (≤6 months) drug regimens for drug-sensitive (DS) and multidrug-resistant (MDR)-TB treatment. Costs per regimen were estimated by multiplying recommended drug amounts with 2021 Global Drug Facility prices and drug import costs of a TB program in Karakalpakstan, Uzbekistan. The standard short-course treatment of DS-TB requires taking 730 fixed-dose combination tablets, which weigh 0.79 kg and cause an import cost of $4.19 (9.8% of the regimen’s drug cost of $43). A new 4-month DS-TB regimen requires taking 1358 tablets, which weigh 1.1 kg and cause an import cost of $6.07 (2.6% of the regimen’s drug cost of $233). MDR-TB regimens that last between 24 weeks and 20 months involve 546-9368 tablets and injections. The drugs for these MDR-TB regimens were estimated to weigh 0.42-96 kg and cause an import cost of $2.26-507 per drug regimen (0.29-11% of a regimen’s drug cost of $360-15,028). In a multivariable regression analysis, an additional treatment month increased the import cost of a drug regimen by $5.45 (95% CI: 1.65 to 9.26). Use of an injectable antibiotic in a regimen increased the import cost by $133 (95% CI: 47 to 219). The variable and potentially sizable import costs of TB regimens can affect the financial needs of TB programs. Drug regimens that are shorter and all-oral tend to reduce import costs compared to longer regimens and regimens including an injectable drug.
Gesehen am 29.05.2024
Keywords: Forschungsdaten; Datenbank